Modern Approaches to the Management of Children with Hypophosphatasia - Aleksander A. Baranov; Tatiana T. Batysheva; Olga V. Bykova; Nato D. Vashakmadze; Elena V. Vislobokova; Alisa V. Vitebskaya; Elena A. Vishneva; Victoria Yu. Voynova; Natalia V. Zhurkova; Ekaterina Yu. Zakharova; Larisa P. Kisel'nikova; Mikhail M. Kostik; et al. (Union of pediatricians of Russia, 2023)
Hypophosphatasia is rare genetic disease caused by tissue-nonspecific alkaline phosphatase deficiency due to the mutation in the ALPL gene. Disease can manifest in utero, in childhood or in adults depending on its form and severity. This article presents modern data on the epidemiology, etiology, and clinical signs of hypophosphatasia in children, covers in details differential diagnostic search, and gives guidelines for its evidence-based treatment. Without timely treatment the prognosis of the disease is unfavorable in most cases. Such patients require follow-up by multidisciplinary team of physicians. The only effective method of treatment is enzyme replacement therapy with asfotase alfa. Symptomatic therapy is also crucial as well as physiotherapeutic procedures and therapeutic exercise programs (at rehabilitation stage).